Penerapan Model Pembelajaran Value Clarification Technique (VCT) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Putri, Era Pazira; Rizal, M. Syahrul; Aprinawati, Iis; Nurhaswinda, Nurhaswinda; Fadhilaturrahmi, Fadhilaturrahmi (MODELING: Jurnal Program Studi PGMI, 2023)
The background of this research is the low critical thinking skills of students in class V UPT SDN 013 Kumantan. Therefore the purpose of this research is to improve students' critical thinking skills in class V UPT SDN 013 Kumantan. This research is a class follow-up research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were 1 teacher and 12 students, while the object was to use the VCT learning model to improve students' critical thinking skills. The research instrument consisted of teacher activity observation sheets, student activity observation sheets, documentation sheets and study test sheets during the learning process using the VCT learning model. While the data analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, at the second meeting of cycle I critical thinking skills. The test results in cycle I meeting 1 showed that there were 5 students (42%) of the 12 students who were included in the less critical category (<69), and in cycle 1 meeting II showed that there were 3 students (25%) of the 12 students who included in the less critical category (<69), while in the second cycle meeting I showed that there were 8 students (67%) out of 12 students who were included in the very less critical category (<69), and in the second cycle the second meeting showed there were 9 students (92%) out of 12 students who were included in the very critical category (<100%). By using the VCT learning model, it can improve the critical thinking skills of class V UPT SDN 013 Kumantan students. Keywords: Critical Thinking Ability, Value Clarification Technique (VCT)